2010
DOI: 10.1108/00483481011075594
|View full text |Cite
|
Sign up to set email alerts
|

Males' attitudes towards working females in Saudi Arabia

Abstract: Purpose -The purpose of this paper is to fill a gap in the literature on women who work in the Arab Muslim context, reflecting on the experience of Saudi Arabia. Design/methodology/approach -A sample of 301 male participants completed the newly developed multidimensional aversion to women who work scale (MAWWWS). Findings -The paper reveals that Saudi males report very traditional attitudes towards working females. Moreover, the single, unemployed, young and educated Saudi males report less traditional attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 50 publications
2
101
0
1
Order By: Relevance
“…In the past, the father or the breadwinner made most major family decisions [20]. However, modernization changed the role of women, and provided them with more opportunities [20,21]. Women's autonomy is important to ensure healthy child outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the father or the breadwinner made most major family decisions [20]. However, modernization changed the role of women, and provided them with more opportunities [20,21]. Women's autonomy is important to ensure healthy child outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural influences impact parenting beliefs, goals, and values, which in turn influence parenting styles and practices [10,19]. In Saudi communities, women's role is primarily as housewives and child caregivers [20][21][22]. In the past, the father or the breadwinner made most major family decisions [20].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study (Elamin & Omair, 2010) demonstrated that Saudi men present traditional attitudes toward Saudi women in the workplace. The authors indicated that the participants presented strongly held beliefs on gender stereotypes that view men as capable of taking on leadership roles, whereas women were prescribed to domestic and child rearing responsibilities.…”
Section: Challenges and Barriers Facing Female Leaders In Saudi Arabiamentioning
confidence: 78%
“…Thus, justifying men's authority over women (Metcalfe, 2011). However, such an explanation tends to overlook the fact that such cultural and social processes exploit Islam's spirit and ideals to legitimize the defined submissive roles of Muslim women (Elamin & Omair, 2010;Kauser & Tlaiss, 2011).…”
Section: Female Leadership In the Gcc Statesmentioning
confidence: 99%
See 1 more Smart Citation